2018
DOI: 10.1159/000493469
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hyperfiltration: An Early Marker of Nephropathy in Fabry Disease

Abstract: Background and objectives: Progressive nephropathy is one of the main features of Fabry disease (FD). It has been supposed that an early phase, clinically silent disease occurs in childhood and adolescence and is characterized by glomerular hyperfiltration (HF). Surprisingly, although HF has been reported in several studies, its prevalence is at present unknown. The focus of our study was to determine the prevalence of HF in a cohort of patients with FD and to identify the factors associated with a high risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
(60 reference statements)
1
19
0
2
Order By: Relevance
“…The detection of a major prevalence of GHF in the first quartile of age is coincident with the natural evolution of Fabry nephropathy in patients without specific treatment. A recent retrospective observational study in Italy showed a similar result with a GHF prevalence of 24% in a population of 87 FD patients (20).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The detection of a major prevalence of GHF in the first quartile of age is coincident with the natural evolution of Fabry nephropathy in patients without specific treatment. A recent retrospective observational study in Italy showed a similar result with a GHF prevalence of 24% in a population of 87 FD patients (20).…”
Section: Discussionsupporting
confidence: 57%
“…In Argentina, a recent analysis of young patients with classic FD forms and mild or absent nephropathy showed urinary microRNAs suggestive of kidney fibrosis, even in non-albuminuric cases (22). Riccio et al reported that GHF may be an early marker of renal involvement in FD patients, even before the onset of signs, symptoms, or laboratory changes (20). Although proteinuria can be considered an indirect marker of GHF, there are situations where the urinary protein loss is due to alterations in the glomerular filtration barrier secondary to a glomerular disease rather than a consequence of the GHF per se.…”
Section: Discussionmentioning
confidence: 99%
“…When injured, the result is glomerulosclerosis, indicative of irreversible damage to the glomeruli. [67][68][69] Endothelial cells contribute to the development of fibrosis, through luminal obstruction and ischemia. 70 The mesangial cells seem to play a less important role in the pathophysiology of nephropathy.…”
Section: Clinical and Laboratory Findingsmentioning
confidence: 99%
“…Some Fabry patients develop GFR loss before development of proteinuria [16]. Glomerular hyperfiltration may be a common feature in young Fabry patients and may be considered as an early marker of Fabry nephropathy [40], which masks impairment of renal function, although rare, a decline in GFR can already be seen in adolescence [41]. Slope of progression of renal insufficiency was correlated to the level of proteinuria and in addition, it was not linear as shown by Schiffmann et al, where they retrospectively analyzed the decline of eGFR.…”
Section: Serum Creatinine and Glomerular Filtration Rate (Gfr)mentioning
confidence: 99%